Tourism of such maritime in the form of activity addressed to wide society exploitedly is environmental service of coastal area and go out to sea. Development of coastal area for recreation these days tend to increase, others the tourism also to support local economics .. Kalianda Resort own some facility which complete enough as a(n) area tourism therefore draw to conduct research hit model of request recreation of maritime tourism in Kalianda Resort with model of travel cost. Traveling expense - Moch Prihatna Sobari; Gatot Yulianto; Desi Nurita (Buletin Ekonomi Perikanan, 2006)
Tourism of such maritime in the form of activity addressed to wide society exploitedly is environmental service of coastal area and go out to sea. Development of coastal area for recreation these days tend to increase, others the tourism also to support local economics .. Kalianda Resort own some facility which complete enough as a(n) area tourism therefore draw to conduct research hit model of request recreation of maritime tourism in Kalianda Resort with model of travel cost. Traveling expense of mean reckoned from a transportation; released by each; every visitor from same zona. Visitor coming from outside Provinsi Lampung more opting generally to stay with consanquinity, friend, or the cheaper lodging in Bandar Lampung, so that some visitor coming from outside Provinsi Lampung to conduct dot of departure from 'Bandar Lampung. Traveling expense of mean which its amount at least that is from zona of Metro and traveling expense of biggest mean is from zona Serang. Demand curve depicted to follow constant elasticity model with price elasticity value equal to 2,4759, meaning all changes in traveling expense equal to 1%, hence mount tourist visit will change equal to 2,4759%. Relation of between traveling expense mean ( P) with visit storey (0) from its correlation coefficient that is 0,79. The correlation coefficient value express that relation! Which enough sliver between P by 0, negative value from correlation coefficient show adversative direction meaning if traveling expense ( P) mount hence mount visit ( 0) will be downhill, conversely. Result from analysiS SWOT can be depicted in diagram analysis SWOT. From calculation result got the ordinate and abscissa dot (0,152;0,259) which lay in kuadran 1. position kuadran 1 representing situation that very beneficial, where organizer Kalianda Resort own strength and opportunity which can be exploited better. Correct strategy for this condition is support aggresive development policy.